2020
DOI: 10.1002/acr.23875
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Cardiovascular Events With Biologic and Synthetic Disease‐Modifying Antirheumatic Drugs in Patients With Rheumatoid Arthritis: A Systematic Review and Meta‐Analysis

Abstract: Objective We performed a systematic review and meta‐analysis to evaluate the comparative effects of tumor necrosis factor inhibitors (TNFi), non‐TNFi biologics, and conventional synthetic disease‐modifying antirheumatic drugs (csDMARDs) on cardiovascular risk in rheumatoid arthritis (RA). Methods Using a systematic search through May 8, 2018, we included 14 observational studies in adults with RA treated with TNFi, non‐TNFi biologics, tofacitinib, or csDMARDs, reporting the risk of major adverse cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 28 publications
5
88
1
3
Order By: Relevance
“…The RA-field is no exception, as e.g., clearly shown by an SR of in vivo animal experiments published in the "Annals of the Rheumatic Diseases" and "Arthritis and Rheumatism" [41]. Recent SRs of human RA studies did not describe percentages of included studies reporting experimental details [42,43], restricting the interpretation of our data in relation to theirs.…”
Section: Discussionmentioning
confidence: 88%
“…The RA-field is no exception, as e.g., clearly shown by an SR of in vivo animal experiments published in the "Annals of the Rheumatic Diseases" and "Arthritis and Rheumatism" [41]. Recent SRs of human RA studies did not describe percentages of included studies reporting experimental details [42,43], restricting the interpretation of our data in relation to theirs.…”
Section: Discussionmentioning
confidence: 88%
“…Followed observation on cholesterol increase in tocilizumab-treated RA patients, the interest on impact of various biologic and non-biologic DMARDs increased significantly. tocilizumab, an IL-6 receptor inhibitor, increases circulating LDL levels [ 77 ], but no increased risk of major cardiovascular events was observed [ 78 , 79 ]. It is established that tocilizumab reduces the LDL hypercatabolic state and diminishes the expression of LDL receptor on hepatocytes via a proprotein convertase subtilisin/kexin type-9-mediated mechanism [ 80 , 81 ].…”
Section: Safety Issues Of Jak Inhibitorsmentioning
confidence: 99%
“…Several of these cytokines have been associated with myocardial and vascular dysfunction including arterial stiffness (Pryshchep et al, 2006;Yong et al, 2013), coronary atherosclerosis (Zhang et al, 2006), left ventricular hypertrophy and cardiac remodelling (Madhur et al, 2010;Sheu et al, 2013) and myocardial ischaemia (Ikonomidis et al, 2005(Ikonomidis et al, , 2017. IL-17A, one of the main inflammatory mediators in psoriasis (Lockshin, Balagula, & Merola, 2018), has pro-atherogenic action (Karbach et al, 2014) and has been detected in patients with acute coronary syndromes (Cheng et al, 2008).…”
Section: Pathogenetic Mechanismsmentioning
confidence: 99%
“…Anti‐IL‐1 regimens seem to have a more favourable profile on myocardial function when compared to anti‐IL‐6 regimens, whereas anti‐IL‐6 regimens mostly benefit vascular function (Ikonomidis, Pavlidis, et al, 2019). In addition, two recent meta‐analyses indicated that tocilizumab (an anti‐IL‐6 agent) is safe in terms of CV outcomes compared to disease‐modifying antirheumatic drugs (Castagné et al, 2019) and may also be associated with decreased risk of major adverse cardiovascular events in comparison to TNF‐α inhibitors (Singh et al, 2019).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%